2005
DOI: 10.1007/bf02893374
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating B cell immunoglobulin variable region gene usage in invasive ductal breast carcinoma

Abstract: A major focus of tumor immunology is to reveal the potential role and capacity of immunocompetent cells found in different solid tumor tissues. The most abundant infiltrating cells (TIL), the T lymphocytes have been investigated in details concerning T-cell receptor usage and specificity. However, B cells have hardly been investigated in this respect, although high cellular B-cell infiltration has been correlated with improved patients' survival in some breast carcinomas. This led to our objectives to study va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…(No report assayed VL usage.) Two studies performed microdissection of a small number of B cell follicles identified in tumors that also included limited numbers of PCs, cloning VH with class-independent primers that do not reveal Ig type [37,38]. As noted above, normal breast epithelium and breast cancers with small-to-moderate PC reaction are typically dominated by IgA PCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…(No report assayed VL usage.) Two studies performed microdissection of a small number of B cell follicles identified in tumors that also included limited numbers of PCs, cloning VH with class-independent primers that do not reveal Ig type [37,38]. As noted above, normal breast epithelium and breast cancers with small-to-moderate PC reaction are typically dominated by IgA PCs [28].…”
Section: Discussionmentioning
confidence: 99%
“…TIL-Bs appear early during breast tumorigenesis, being present at the ductal carcinoma in situ stage (49). TIL-Bs generally express IgG and show evidence of Ag-driven expansion and somatic mutation consistent with affinity maturation (50)(51)(52)(53)(54)(55). In one IgG sequencing study, .45% of TIL-B belonged to a clonal group, and there were 4-11 major clonal groups per tumor (46).…”
Section: B Cells In Cancermentioning
confidence: 99%
“…These dual effects may be due to the tumor cells and/or the inflammatory context. The case of B lymphocytes is also unclear: they correlate with tumor growth and invasion in murine models [44][45][46][47] but scarce observations associate a B cells signature to good prognosis in several human cancers [48][49][50]. Intratumoral NK cells have been reported to down regulate their activating receptors and to be associated to larger breast [51] and lung [28] tumors, but without clear impact on patients survival.…”
Section: The Immune Contexture Of the Tumor Microenvironment Has A Mamentioning
confidence: 99%